Fast targeted analysis of 132 acidic and neutral drugs and poisons in whole blood using LC-MS/MS. - Di Rago, Matthew; Saar, Eva; Rodda, Luke N; Turfus, Sophie; Kotsos, Alex; Gerostamoulos, Dimitri; Drummer, Olaf H (Forensic Science International, 2014)
The aim of this study was to develop an LC-MS/MS based screening technique that covers a broad range of acidic and neutral drugs and poisons by combining a small sample volume and efficient extraction technique with simple automated data processing. After protein precipitation of 100μL of whole blood, 132 common acidic and neutral drugs and poisons including non-steroidal anti-inflammatory drugs, barbiturates, anticonvulsants, antidiabetics, muscle relaxants, diuretics and superwarfarin rodenticides (47 quantitated, 85 reported as detected) were separated using a Shimadzu Prominence HPLC system with a C18 separation column (Kinetex XB-C18, 4.6mm×150mm, 5μm), using gradient elution with a mobile phase of 25mM ammonium acetate buffer (pH 7.5)/acetonitrile. The drugs were detected using an ABSciex(®) API 2000 LC-MS/MS system (ESI+ and -, MRM mode, two transitions per analyte). The method was fully validated in accordance with international guidelines. Quantification data obtained using one-point calibration compared favorably to that using multiple calibrants. The presented LC-MS/MS assay has proven to be applicable for determination of the analytes in blood. The fast and reliable extraction method combined with automated processing gives the opportunity for high throughput and fast turnaround times for forensic and clinical toxicology.